Recalculating default values for palm oil - Gernot Pehnelt; Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
On 05 December 2010, the Renewable Energy Directive (RED) came into force in the EU. Member States are still working to fully transpose the Directive into national law and establish a framework for achieving their legally binding greenhouse gas (GHG) emission reductions. However, governments got off to a slow start as debate continues on the validity of the directives foundations including the default values used to measure the sustainability of biofuels. Only sustainable biofuels can be counted towards Member State targets. This, as a matter of principle, makes sense with respect to the very aim of renewable energy policies. On the other hand, the vague and distortive formulation and values regarding what is to be classified as sustainable have negatively impacted the perception of the underlying scientific base and methodologies as well as the reliability in the European biofuels sector. This uncertainty and the ongoing controversial debates are affecting investment and progress in the biofuel sector not just in Europe but all over the world. Producers of soybeans in the US, sugarcane in Brazil and palm oil in Malaysia and Indonesia as well as European importers and end-users of these products have all been sharply critical of the default values, citing significant variations in calculations that undermine the credibility of the values contained in the Directive. Given the remarkable difference between the calculation of carbon reduction performance of palm oil based biofuel by the EU and a range of scientific studies which we documented in an earlier paper (Pehnelt and Vietze 2009), we are re-calculating GHG emissions saving potentials for palm oil biodiesel in order to further assess the carbon footprint of palm oil to overcome the lack of transparency in existing publications on the issue and EU regulations governing the biofuel feed-stocks. The aim of this paper is to calculate realistic and transparent scenario based CO2-emission values for the GHG emission savings of palm oil fuel compared with fossil fuel. Using the calculation scheme proposed by the Renewable Energy Directive (RED), we derive a more realistic overall default value for palm oil diesel by using current input and output data of biofuel production (e.g. in South-East Asia) and documenting every single step in detail. We calculate different scenarios in which reliable data on the production conditions (and the regarding emission values during the production chain) of palm oil diesel are used. Our conservative calculations based on the Joint Research Centre's (JEC 2011) background data and current publications on palm oil production result in GHG emissions saving potentials of palm oil based biodiesel fairly above the 35% threshold. We cannot reproduce the EU's GHG saving values for palm oil. Rather, our results confirm the higher values obtained by other studies mentioned in our last paper (Pehnelt and Vietze 2009) and elsewhere in this study. Our results indicate default values for the GHG emission savings potential of palm oil biodiesel not only way beyond the 19 percent default value published in RED but also beyond the 35 percent threshold. Our findings conclude that the more accurate default value for palm oil feedstock for electricity generation to be 52%, and for transportation biodiesel between 38.5% and 41%, depending on the fossil fuel comparator. Our results confirm the findings by other studies and challenge the official default values published in RED. As indicated by lawsuits filed by environmental NGOs against the Commission for greater transparency related to the assessment of biofuels, the process has been severely lacking in full disclosure of metrics used to achieve the values contained in the Renewable Energy Directive. As a result, the reliability of the Directive to support the EU's low-carbon ambitions is being undermined, exposing the EU and Commission to charges of trade discrimination and limiting the ability of Member States to achieve their legally binding GHG emission reductions. This analysis demonstrates that a full review of the values contained in the Directive should be undertaken and the values revised to ensure their accuracy, and raises questions as to the method that the values were originally established. Were outside parties consulted, including the industries directly affected by the assessments in the Directive? Were these values peer reviewed? In light of grievances expressed by producers throughout the world, including US soybean growers, Brazilian sugarcane farmers, and Malaysian and Indonesian palm growers, ensuring the Directive does not discriminate against imports is critical to the long-term efforts in the EU to reduce GHG emissions.
Keywords: F14; F18; O13; Q01; Q15; Q27; Q56; Q57; 330; biofuel; palm oil; Biodiesel; RED; Renewable Energy Directive; default values; GHG-emissions; Palmöl; Pflanzenbau; Bewertung; Bioenergie; Klimaschutz; Förderung regenerativer Energien; EU-Umweltpolitik